Sing Beling Sing Nganten: Symbolic Power, Habitus, and Gender in Urban Balinese Society - Yogiswari, Krisna Sukma; Maharani, Septiana Dwiputri; Nugroho, Hastanti Widy (Universitas Pendidikan Ganesha, 2025)
Sing beling sing nganten, literally meaning “not pregnant, not married,” is a social phenomenon widely found in Balinese society, particularly in urban areas. This practice implicitly reflects symbolic power rooted in social habitus and gendered expectations related to fertility, marriage, and women's roles. This study aims to examine how Pierre Bourdieu’s concepts of habitus and symbolic power operate in the normalization of this practice. Employing a qualitative approach, data were collected through in-depth interviews and participatory observation involving 15 informants, including women, men, traditional leaders, and scholars. The data were analyzed using Interpretative Phenomenological Analysis (IPA) to explore participants’ lived experiences, and Critical Discourse Analysis (CDA) to uncover the linguistic mechanisms that reproduce symbolic domination. The findings reveal that sing beling sing nganten functions as a social practice that disciplines women’s bodies through everyday language, social expectations, and religious narratives. Symbolic power legitimizes fertility as a prerequisite for marriage and reinforces patriarchal values through discourses perceived as “natural.” This study contributes to the understanding of gender norm reproduction in modern contexts and suggests the need for future research to explore possibilities for social transformation.